PERUBAHAN BENTUK KALIMAT PASIF BAHASA INGGRIS KE DALAM BAHASA INDONESIA PADA NOVEL MORNING, NOON AND NIGHT KARYA SIDNEY SHELDON - Mohammad Rizqi (TELAGA BAHASA, 2017)
This paper focused on English passive voice translation into Indonesian. An active voice is a sentence where the subject performs the action stated by the verb, and a passive voice is the subject is acted upon by the verb. The active voice that can be switched into a passive voice is an active voice that has an object. Thus, the sentence is a transitive form. The method used is a qualitative method by using a technique of text content analysis and the text are English novel and its translation in Indonesian novel. This research is an analysis description on the novel that included passive voice translation and structural shift. This paper explained the results of the study of the passive sentences of the source language (English) translated into Indonesian. The results of the study show that not all of the passive sentences of the source language can be translated in the form of passive sentences in target language. Instead, the passive sentences can be translated in the form of active sentences because of the meaning contained.